Transjugular LuX-Valve Plus Transcatheter Tricuspid Valve Replacement for Torrential Tricuspid Regurgitation in a Patient With a Giant Right Atrium and Prior Multiple Valve Interventions: A Case Report - Quntai Qiu; Xinlei Wu; Daozhu Wu; Xinmin Zhang; Lianpin Wu (European Heart Journal - Case Reports, 2026)
Abstract Background Transcatheter tricuspid valve replacement (TTVR) is an option for selected patients with severe tricuspid regurgitation (TR) who are at high surgical risk, but experience remains limited in those with extreme right-heart anatomy, including a giant right atrium and a markedly enlarged elliptical tricuspid annulus. Case summary A 62-year-old man was admitted with progressive dyspnoea and lower-extremity oedema (NYHA class IV). He had prior mechanical mitral valve replacement and transcatheter aortic valve replacement. Echocardiography and CTA showed torrential TR, a giant right atrium (11.59 × 7.73 cm), preserved right ventricular systolic function, and a markedly elliptical annulus with a perimeter-derived diameter of 55.5 mm. Persistent TR despite satisfactory left-sided prosthetic valve function prompted transcatheter evaluation. Redo surgery was prohibitive and transcatheter edge-to-edge repair unsuitable. The Heart Team selected LuX-Valve Plus because its leaflet graspers and septal anchor provide radial force-independent multipoint fixation. A 79.2-mm bend-point-to-annulus distance exceeded the proposed 45–70 mm range, requiring a slightly lateral jugular entry angle and complicating depth control and coaxial alignment. The mechanical mitral prosthesis limited transoesophageal echocardiography (TEE) but served as a fluoroscopic landmark; TEE and fluoroscopy enabled successful implantation. At 1 month, NYHA class improved to II, with stable prosthetic haemodynamics, no obvious transvalvular regurgitation, and trivial paravalvular leak; findings remained stable at 6–7 weeks. Discussion This case highlights the feasibility of transjugular LuX-Valve Plus TTVR in extreme right-heart anatomy and emphasizes the importance of anatomy-driven device selection, tailored delivery and imaging strategies, and individualized postprocedural management.